The 5′ Arm of Kluyveromyces lactis Telomerase RNA Is Critical for Telomerase Function - Kabaha, Majdi M. (American Society for Microbiology (ASM), 2008)
Telomerase is a ribonucleoprotein reverse transcriptase that copies a short template within its integral telomerase RNA moiety (TER) onto eukaryotic chromosome ends, thus compensating for incomplete replication and degradation. The highly divergent yeast TER is structured in three long arms, with a catalytic core at its center. A binding site for the protein Ku80 is conserved within the 5′ arm of TER in Saccharomyces but not in Kluyveromyces budding yeast species. Consistently, KU80 deletion in Kluyveromyces lactis does not affect telomere length, while it causes telomere shortening in Saccharomyces cerevisiae. We found elements in the 5′ arm of K. lactis TER that are crucial for telomerase activity and stability. However, we found no indication of the association of Ku80 with this arm. Although the overexpression of Ku80 rescues a particular mutation in K. lactis TER1 that phenocopies a telomerase null mutation, this effect is indirect, caused by the repression of the recombination pathway competing for telomere maintenance. Interestingly, the overexpression of Est3, an essential telomerase protein whose function is still unknown, suppresses the phenotypes of mutations in this arm. These results indicate that the 5′ arm of K. lactis TER has critical roles in telomerase function, which may be linked to the function of Est3.